Effect of Amino Sugars on Platelet Aggregation and on Fibrinogen Binding - Kinlough-Rathbone, Raelene L; Packham, Marian A; Mustard, J Fraser (Thrombosis and Haemostasis, 1984)
The amino sugars glucosamine, galactosamine and man- nosamine (30 mM) inhibited aggregation of human or rabbit platelets induced by ADP, collagen, thrombin, PAF or high concentrations of sodium arachidonate. 125I-fibrinogen binding during ADP-induced aggregation, and release of amine storage granule contents were also inhibited. Increasing the calcium concentration of the suspending medium to 5 mM did not overcome the inhibitory effect on the release reaction.The amino sugars deaggregated rabbit platelets that had been aggregated by ADP, collagen or thrombin, but deaggregated human platelets readily only when ADP was used as the aggregating agent. Fibrinogen-induced aggregation of chymotrypsin-treated platelets was blocked by the amino sugars. They did not inhibit platelet adherence to a collagen-coated glass surface, nor affect release of granule contents from the adherent platelets. Aggregation and release induced by low concentrations of sodium arachidonate or the divalent cation ionophore A23187 were potentiated, indicating that the effects of the amino sugars on platelets are more complex than simple inhibition of the lectinlike activity that becomes available on the surface of platelets that have undergone the release reaction. One of the effects of the amino sugars, however, is interference with the binding of fibrinogen to platelets. The effects of the amino sugars are shared by other primary amines.
Keywords: Platelet aggregation; Fibrinogen binding; Amino sugars